2016
DOI: 10.1158/2159-8290.cd-16-0154
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Copy Number Dictates a Gene-Independent Cell Response to CRISPR/Cas9 Targeting

Abstract: The CRISPR-Cas9 system enables genome editing and somatic cell genetic screens in mammalian cells. We performed genome scale loss-of-function screens in 33 cancer cell lines to identify genes essential for proliferation/survival and found a strong correlation between increased gene copy number and decreased cell viability after genome editing. Within regions of copy number gain, CRISPR-Cas9 targeting of both expressed and unexpressed genes, as well as intergenic loci, led to significantly decreased cell prolif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
571
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 517 publications
(614 citation statements)
references
References 48 publications
22
571
0
4
Order By: Relevance
“…1D). Furthermore, we investigated the gene copy number effects on CRISPR screen performance and confirmed that genes in genomic amplified regions tend to exhibit more negative selection as revealed by recent studies (16,26) (Fig. S1D and Dataset S1).…”
Section: Resultssupporting
confidence: 74%
“…1D). Furthermore, we investigated the gene copy number effects on CRISPR screen performance and confirmed that genes in genomic amplified regions tend to exhibit more negative selection as revealed by recent studies (16,26) (Fig. S1D and Dataset S1).…”
Section: Resultssupporting
confidence: 74%
“…In aneuploid cancer cell models, the genes located in amplified regions scored as lethal, indicating false positive results as already described by Aguirre et al (32). Thus, the number of loci representing the gene of interest in a cancer cell line under investigation is of crucial importance for the physiological response to CRISPR/Cas9 and for the experimental interpretation.…”
Section: Discussionmentioning
confidence: 71%
“…Two recent studies demonstrated that CRISPR/Cas9 is not suitable in cellular cancer models showing gene amplifications, as overrepresented genomic regions cause false positive results. Aguirre et al (32) provided evidence that DNA breaks generated by the CRISPR/Cas9 system lead to gene-independent cell toxicity and the number of DNA cuts rather than the gene knockout predicts the cellular response.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple approaches fied. Cell lines stably expressing Cas9 were generated and Cas9 activity confirmed as previously described (26). Stable cell lines were then transduced with the Avana library and passaged in triplicate for 21 days, and the relative enrichment or depletion of guides was assessed using massively parallel sequencing and compared with the initial plasmid pool.…”
Section: Crispr-cas9 Screen Reveals a Mycn-amplified Neuroblastoma Dementioning
confidence: 99%
“…Stable cell lines were then transduced with the Avana library and passaged in triplicate for 21 days, and the relative enrichment or depletion of guides was assessed using massively parallel sequencing and compared with the initial plasmid pool. Data were normalized across cell lines, and a gene-level dependency score was calculated using the recently described CERES algorithm that takes into account the increased "cutting toxicity" observed in regions of copy number gain (24,26). We then identified preferential genetic dependencies in neuroblastoma cell lines by applying independent component analysis (ICA) (27,28) to the CRISPR-Cas9 data.…”
Section: Crispr-cas9 Screen Reveals a Mycn-amplified Neuroblastoma Dementioning
confidence: 99%